Picture This! Teaching Poetry with Visual and Textual Representation - Jansen, Michael (My University, 2010)
Oftentimes, there is much abstraction and symbolism in poetry and, by complementing the text with visuals that convey a similar message, we as teachers can provide another avenue for our students to understand the intended message of the author. The presentation speaks to the need of language learners to have access to materials in their target language in multiple modes, catering to the needs of the multiple learning styles represented in the classroom. This presentation works to examine the poetry of Veronica Volkow in her work Arcanos and how the visuals and text therein complement themselves to convey a similar message.
Color poster with text and images.
Keywords: Posters; Volkow, Veronica. Arcanos; Mexican poetry--Study and teaching; Mexican poetry--Audio-visual aids; Poetry--Audio-visual aids; Poetry--Study and teaching